Xenophobia and Political Tolerance of Lithuanian High School Students - Sprindžiūnas, Andrius (Acta Paedagogica Vilnensia, 2006)
The article focus on the methodological problems of the research of the political tolerance, particularly of the method of the "least liked groups" as conducted in some western countries and Lithuania. It also represents data of recent survey of the political tolerance among Lithuanian high school students towards members of some social groups. According to the survey young Lithuanians are most tolerant to the people of other races (not white) by expressing willingness to ensure then main civil freedoms including right to teach in public schools, also to very religious and AIDS infected persons. On the other hand most intolerant attitudes were observed to militarists, communists and anti-globalists. The data encouraged further investigations whether these tendencies reveal a true tolerance and mature civil position or were determined by factors like inherited preconceptions and dogmatic thinking.
Keywords: school; xenophobia; political tolerance; inherited preconceptions; dogmatic thinking